Since you said both -51 and -50,, I was not entirely sure which one to do. I'm solving this for -50 instead of -51,, but if it is actually -51 let me know and I will fix my answer for you :).
When there is a "-" sign in front of the parenthesis,, you must change the sign of each term in the parenthesis. This will look like the following:
-50 = a + 27
Next,, move the variable to the left side and change its sign.
-a - 50 = 27
Now move the constant to the right side and change its sign.
-a = 27 + 50
Add the two numbers together
-a = 77
Lastly,, change the signs on both side of the equation to get your final answer.
a = -77
This means that the correct answer to your question is a = -77.
Let me know if you have any further questions
:)